Longitudinal study of Canadian correctional workers' wellbeing, organizations, roles and knowledge (CCWORK): Baseline demographics and prevalence of mental health disorders - Easterbrook, Bethany; Ricciardelli, Rosemary; Sanger, Brahm D.; Mitchell, Meghan M.; McKinnon, Margaret C.; Carleton, R. Nicholas (Frontiers in Psychiatry, 2022)
Background: Researchers and practitioners have begun to recognize and empirically examining the mental health challenges facing public safety personnel (PSP). Empirical results from longitudinal data collections among PSP remains extremely scant, particularly for institutional correctional workers. We designed the current study to assess the mental health of Correctional Service of Canada (CSC) correctional officer recruits (CORs) across time to help clarify potential challenges to or protective factors for mental health across correctional officer (CO) careers. Methods: The current study uses data from the Canadian Correctional Workers’ Well-being, Organizations, Roles, and Knowledge (CCWORK) study. The study uses a longitudinal design with self-report surveys administered online prior to CORs beginning the CSC Correctional Training Program. Initial baseline survey data were used to assess demographic information and mental health symptoms endorsed at the outset of the training program. Results: Participating CORs (n=265; 40% female; age = 32.6, SD = 9.1) began training between August 2018 and July 2021. Participants were less likely to screen positive for one or more current mental health disorders (i.e., 4.9%) than previously published rates for serving correctional officers (i.e., 54.6%), including reporting lower rates of posttraumatic stress disorder (i.e., 2.4% vs. 29.1%) and major depressive disorder (i.e., 1.9% vs. 31.1%). Conclusion/Impact: Prevalence of positive screens for current mental health disorders in CORs appears lower than for the general population, and significantly lower than for serving correctional officers. The current results suggest an important causal relationship may exist between correctional work and detrimental mental health outcomes. Maintaining the mental health of correctional officers may require institutionally-supported proactive and responsive multimodal activities.